Analisis Disiplin Kerja Guru SMK Swasta Taruna Pekanbaru - harwina, yulia (Komunitas Manajemen Kompetitif, 2016)
Abstract: Labor discipline is business as management implementation guidelines to strengthen the organization in achieving its intended purpose. The better the teacher labor discipline in terms of providing a form of business confidence for menuakinkan in order to understand the rules that exist in schools and also strive to adhere to the rules defined. Then have a keen desire to change is a positive attitude or also repairs done continuously by teachers in order to improve discipline in work. Also in the sacrifice of the efforts of teachers in making the work done iklas follow the rules that exist and also the attitude of openness in their duties. In terms of the value achieved is the result obtained in the form of real action of a teacher and an attitude of self-discipline that views of his actions every day as well as the achievement is the result of discipline that can be seen from the extent of the violations committed and compliments received by teachers in the discipline. Keywords: Work Discipline Vocational Teachers